A review on characteristics and analytical methods of atovaquone – a potent antimalarial agent - Sharma, Sanyam; Sharma, Rahul; Devi, Arti; Jindal, Shammy; Goyal, Kamya (Creative Pharma Assent, 2020)
Drugs used in the treatment of malaria that is caused by various plasmosium species i.e. P. falciparum, P. vivax are most irresistible disease throughout the world. The different medications are utilized in the treatment of malaria incorporated the Aryl aminoalcohol mixes: Quinine, Quinidine, Chloroquine, Mefloquine; Antifolate compound: Pyrimethamine, Proguanil, Chlorproguanil, Trimethoprim and Atovaquone. Atovaquone is most effective drug utilized in the treatment of malaria. It must be given in single or in mixture with different antimalarials. An enormous number of methodologies including High Performance Liquid chromatography (HPLC), UV–Visible spectroscopy and Liquid Chromatography-Mass Spectroscopy (LC-MS) are utilized for the determination of atovaquone. Various analytical methods are used for the analysis of pharmaceutical products and these methods were validated according to ICH guidelines (Q1A R2). Thus, this technique can be safely used for the standard quality control analysis of atovaquone.